Globalisation and pedagogy space, place and identity - Edwards, Richard (Routledge, 2008)
With different pedagogic practices come different ways of examining them and fresh understandings of their implications and assumptions. This book offers an examination of these changes and developments. It examines a number of questions posed by the rapid march of globalisation.